Aspectos biopsicossociais e sexuais entre mulheres climatéricas em uma região do sul do Brasil: um estudo quantitativo - Prieto, Nathalia Guarienti (2021)
Climacteric is a physiological, natural and genetic phenomenon that produces several changes in middle-aged women. Differences in thoughts, beliefs, habits, concepts, in addition to hot flashes, sweating, changes in sleep and rest patterns are some of the characteristic changes in this transitory period. Sexual changes were an important aspect mentioned by the authors, where women reported changes in libido and in the frequency with which they practice sexual activity, both aspects permeated and delimited the biopsychosocial of women between 45 and 65 years old. This study carried out a survey of quantitative data based on the responses of patients undergoing treatment at the Climacteric outpatient clinic of the University Hospital of Santa Maria (HUSM) and at the Primary Health Care (APS) of São Sepé. The aim of the present study was to analyze the biopsychosocial profile of the women attended at the Climacteric outpatient clinic of the HUSM and at the APS of the Municipality of São Sepé and to identify their main morbidities in the period. A structured questionnaire was applied to 131 women with a mean age of 55.13 years, most of them between 55 and 59 years. With regard to education, 66.1% of them studied until completing elementary school, which characterizes a low-income public. The main results were presented and discussed through thematic chapters. The data found regarding the life habits of this population showed a high percentage of women (26.7%) who use tobacco in their middle age, still, (71.5%) are women who are not in the habit of performing physical activity. Regarding family history, the data found pointed to a higher prevalence of breast cancer within families (34%). Regarding gynecological aspects, it was observed that the mean age at menopause was 47.44 years old. The main point of convergence among women, within the morbidity axis, was the high rate of Systemic Arterial Hypertension (SAH), 52% of women reported living with the disease and still consuming one or more medications daily for its control. The survey also shows expressive data on neuropsychiatric problems in this population, 39% of women said they live with diseases such as depression, anxiety, irritability and emotional lability. Among the most prevalent symptoms in the study, muscle pain ranked first, totaling 77% of the sample, of which 37% reported that muscle pain interfered with their daily activities in an extremely severe way. Symptoms related to irritability (73%), anxiety (63%) and physical and mental exhaustion (61%) were also paramount among respondents. Hot flashes were mentioned in 63% of the responses within some intensity. With regard to the use of medications among climacteric women, the data found drew attention: 81.7% of them use some medication for continuous and daily use. The chapter referring to the sexuality of the women surveyed showed a decrease in the frequency of sexual activity in addition to anorgasmia in 29% of them. Faced with this demand, the analysis of these data is relevant in understanding and interpreting such changes in order to complement Nursing Health Education with women, in addition to improving the bond between researchers and respondents.